(untitled) (Palimpsesto, 2017)
The neoliberal and globalized model has transformed, since the 90s, Latin American social and political context. It has also configured a spectrum of concepts in social sciences that focuses on violent alterations suffered within different orders of experience. These changes are acknowledged in the visions of present time articulated by Latino american narrative. The contributions to cultural analysis that literature offers allow us to approach violence within a multidisciplinary perspective. So, this article presents an exploration of urban neoliberal violence from the novel Piedras encantadas by Rodrigo Rey Rosa.